Identification of kinematic predictors of starting speed in track and field sprinters - Vinogradova O.P. ,; Morozova L.V. ,; Melnikova T.I. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify the kinematic indicators of running steps that determine the effective achievement of starting speed by sprinters. Methods and structure of the study. The subjects, 23 student athletes (age 22.6±3.2 years; weight 77.6±7.4 kg; height 1.78±0.03 m) engaged in athletics, performed six 10-metre sprint tests, which were recorded on video for subsequent kinematic analysis. The correlation coefficient of the kinematic indicators of running steps and running speed during the initial segment of the sprint distance was calculated. Results and conclusions. The expediency of differentiated work on increasing the length of sprinters' running steps in balance with indicators of step frequency, ground contact time, and non-support phase time, which also characterize the deepening of morphofunctional changes that determine the effectiveness of increasing starting speed, has been confirmed.